EFEK SISA ASAM HUMAT DARI KOMPOS JERAMI PADI DAN PENGELOLAAN AIR DALAM MENGURANGI KERACUNAN BESI (FE) TANAH SAWAH BUKAAN BARU TERHADAP PRODUKSI PADI - Ruhaimah Ruhaimah; Asmar Asmar; Mimien Harianti (Jurnal Solum, 2009)
Fe toxicity on recent ricefield has been common problem in ricefield management to increase rice productivity. Adding organic matter like humic acid from any source (such as hay residue compost) and water management (intermitten flooding and continue flooding) can reduce Fe toxicity and it will be able to increase rice yield in one plant season.  But how about in second plant season, this research will found effect of adding humic acid from hay compost residue and water management. The objective of this research was to study the interaction of hay compost humic acid residue effect and water management  on Fe abundant and nutrient uptake and rice yield in recent ricefield.  This research has done by split-split plot design 2 x 4. The main plot which was treatment of water management were permanent flooding and intermitten (P1 and P2). And the  split plot which was  humic acid treatments were Ao = 0 ppm (0 Kg humic acid /Acre), A1= 200 ppm (400 Kg humic acid/A), A2= 400 ppm (800 Kg humic acid/A), A3 = 600 ppm (1200 Kg humic acid /A). Data analysed by statistical methode, if the treatments were significant to be continued by Duncan 05 % analysis.  The result has obtained of this research which was Eh value of soil in flooding and intermitten was decrease in every week because treatment of humic acid in first season. The content of Fe2+ in soil was increase in every week until the 8th week. Value of soil pH until 8th week flooding was increase, and caused P available and P potencial were increase too. Plant growth and yield of rice in second season not better than first season, and for intermitten flooding caused better plant growth and yield of rice.    Keyword :  Fe Toxicity, Humic Acid, water management, Recent Ricefield